Clinical relevance of lipid panel and transaminases according liver steatosis and fibrosis measured by transient elastography (Fibroscan®) - Riegos, Julio César (Journal of Medical Biochemistry, 2020)
Background: Nonalcoholic fatty liver disease (NAFLD) is one of the most frequent causes of chronic liver disease and it is related with co-morbilities as the metabolic syndrome. Transient elastography (Fibroscan®) is a non-invasive method to detect NAFLD using the controlled attenuation parameter (CAP). Methods. Patients with NAFLD were included. Hepatic steatosis was quantified by CAP (dB/m) and liver stiffness by Kilopascals (kPa), and were correlated with lipid profile and aspartate transaminase (AST) and alanine transaminase (ALT) transamase. In the statistical analysis, correlation and multiple regression were used. Mann-Whitney U test was used as non-parametric analysis for comparison of medians Results: One hundred five patients were included. In the multiple regression analysis, we observed an association between hepatic steatosis and total cholesterol (B = 0.021, p = 0.038, Exp (B) = 1.021, I.C = 1.001–1.041) and triglycerides (B = 0.017, p = 0.006, Exp (B) = 1.018 and I.C = 1.005–1.030). In the same way, an association between significant hepatic fibrosis and concentrations of total cholesterol (B = -0.019, p = 0.005, Exp (B) = 0.982 I.C = 0.969–0.995) and AST (B = 0.042, p = 3.25 x 10-4, Exp (B) = 1.043 I.C = 1.019–1.068) independently of age, gender, BMI. Conclusions: Our results suggest that total cholesterol and triglycerides concentrations are associated with liver steatosis and significant hepatic fibrosis are associated with lower total cholesterol and higher AST concentrations in patients with NAFLD according Fibroscan®.